2017
DOI: 10.1016/j.paid.2017.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Growth mindset is not associated with scholastic aptitude in a large sample of university applicants

Abstract: Implicit theories of intelligence have been proposed to predict a large number of different outcomes in education. The belief that intelligence is malleable (growth mindset) is supposed to lead to better academic achievement and students' mindset is therefore a potential target for interventions. The present study used a large sample of university applicants (N = 5,653) taking a scholastic aptitude test to further examine the relationship between mindset and achievement in the academic domain. We found that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 24 publications
6
60
5
1
Order By: Relevance
“…Although this appears to be contrary to some of the literature that advocates a growth mindset as a catalyst for academic achievement (e.g., King, 2012), it is not entirely without support from other researchers (e.g., Bahník & Vranka, 2017) and may point instead to the potential benefits to be gained from students adopting elements from both a fixed and growth mindset.…”
Section: Mindsetcontrasting
confidence: 84%
“…Although this appears to be contrary to some of the literature that advocates a growth mindset as a catalyst for academic achievement (e.g., King, 2012), it is not entirely without support from other researchers (e.g., Bahník & Vranka, 2017) and may point instead to the potential benefits to be gained from students adopting elements from both a fixed and growth mindset.…”
Section: Mindsetcontrasting
confidence: 84%
“…Unlike Blackwell et al (2007), these authors reported a significant but small (β = 0.06, CI95= [0.03, 0.09]) association of growth mindset with pre-study GPA (t(1561) = 3.47, p < .001). Recently in in a large sample of university applicants, Bahník and Vranka (2017) found no association of mindset with scholastic aptitude in university entrants.…”
Section: Background To Reported Mindset Effects On Children's Iq and mentioning
confidence: 87%
“…This call has been widely heeded in education (Yettick, Lloyd, Harwin, Riemer, & Swanson, 2016). These claims have, however, been subject to little independent replication (Bahník & Vranka, 2017). In particular, the claim that mindset intervention in children (10-12 year olds) causes large (> 1 SD) impacts on post-challenge IQ (Mueller & Dweck, 1998) has not been replicated, and no studies have included graded outcome measures (easy and difficult ability items), or active-control conditions, against which intervention effects may be benchmarked, as well as objective measures of external benefits (school grades across time).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of grit in all three domains correlated negatively with the results of the GAP test (see Figure 1 and 2 These data were also used for some analyses of effects of growth mindset in Bahník and Vranka (2017). It is possible to see from Figure 1 that the negative association held for participants within the whole range of abilities and within the whole range of the grit scale.…”
Section: Test Of General Academic Prerequisitesmentioning
confidence: 92%
“…The test has good reliability and it has been shown to correlate highly with the Scholastic aptitude test (SAT; r = .76) and Raven's advanced progressive matrices (r = .5; https://osf.io/xaeu6/). Additional information about the test can be found in Bahník and Vranka (2017) and on https://osf.io/qr8r2/. The analysis was conducted with scores normalized by McCall transformation (McCall, 1939).…”
Section: Test Of General Academic Prerequisitesmentioning
confidence: 99%